Can Board Diversity Promote Dividend Policy? Seeking The Role of Profitability - Muhammad Taufik; Jessica Jessica; Nicken Destriana (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This study investigates the effect of the board of directors (BOD) diversity on dividend policy and how the implications of profitability are treated as moderation. Dividend policy and BOD characteristics have been studied extensively; however, the profitability role being moderating variable and BOD diversity are challenging. To the best of the authors' knowledge, this study is one of the first to examine profitability as moderation. BOD diversity includes gender, age, education level, accounting expertise, and nationality. The research period spanned 2017-2020, where the number of samples was 370 companies listed on the Indonesia Stock Exchange, resulting in 1,480 data. The regression model used is panel data. Overall, BOD gender, education level, and nationality are homogeneous, where female directors, directors with master's education, and foreign directors have a small proportion. As a result, they have no significant effect in promoting dividends. In addition, profitability cannot influence the relationship between board gender and board nationality on dividends. Nevertheless, profitability moderates the relationship between board nationality and dividend policy to a significant negative. Further, board age and accounting expertise positively and significantly affect dividend policy, and the results are identical when moderated by profitability. The proportion of board expertise expressed is heterogeneous, and the board age of 52 years is categorized as old, while they mitigate agency conflict. Thus, companies are required to maintain these proportions. However, companies must remedy the recruitment system to accommodate more female directors, directors with higher education at the master's level, and foreign directors. The government must also refer to regulations in developed and developing countries that establish a minimum quota for the presence of female directors.